WORK READINESS OF MANAGEMENT STUDENTS: THE EFFECTS OF SOFT SKILLS, MOTIVATION, AND PARENTAL ROLE - Alfitri, Diva Salsa (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2025)
This study examines the effects of soft skills, motivation, and parental role on students’ work readiness. An explanatory quantitative approach was employed, involving students from the 2021 cohort of the Management Study Program at ITEBIS PGRI Dewantara Jombang. Data were collected through a questionnaire survey and analyzed to determine the relationships among the variables under investigation. The findings indicate that soft skills, motivation, and parental role significantly affect students’ work readiness. Among these variables, motivation emerged as the most dominant factor in explaining work readiness. These findings underscore that students’ work readiness is shaped not only by non-technical competencies, but also by internal drive for self-development and family support in preparing for future careers. Accordingly, this study highlights the importance of strengthening soft skills, enhancing motivation, and encouraging parental involvement as part of higher education strategies to support students’ work readiness prior to graduation.